ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT KONSUMEN DALAM MEMBELI AIR MINUM ISI ULANG DI DEPOT KOTA PADANG - Sasnelwati, Sasnelwati (Jurnal Ekobistek, 2016)
This Researh aimed to analyze the factors that affect consumer interest in buying refill drinking water, such as; factor of price, service, level of efficiency, and reference. Moreover, the purpose of this study was to determine the most dominant factor influencing consumer interest in buying refill drinking water. The study sample was taken from 100 respondents who made a purchase refill drinking water obtained from drinking water refill depots the city of Padang. Analysis of the data from this study using multiple linear regression were used to determine the factors that affect consumer interest in buying refill drinking water Y = -1.124 + 0.07735X1 + 0.07756X2 + 0.122X3 + e Data processing method of this research is to use SPSS. The analysis showed that significantly overall factors studied enough to affect consumer interest preformance buy refill drinking water F test = 26.825  Based on t test t-test X1 = 3.614, t-test X2 = 2.671, t-test X3 = 4.049 , T test >   t tabel = 1.960, it means was concluded that the most significant factors affect the reference to consumer interest in buying refill drinking water. Based on these results, it is expected to improve strategy for the company to have more attention to the reference factor in deciding and implementing the right marketing strategy in market competition refill drinking water (Depot) in the city of Padang.From the Researh, the service factor is the most dominant factor affecting consumer interest in buying refill drinking water, drinking water, the employer must pay attention to the factors so that will be able to master the refill drinking water market itself. Keywords: the factors that affect consumer interest, buying refill drinking water, Price, Services, Effesieny. Depot in the city of Padang